2007
DOI: 10.1152/ajpregu.00558.2006
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental insufficiency alters nephrogenesis and downregulates cyclooxygenase-2 expression in a model of IUGR with adult-onset hypertension

Abstract: Clinical and animal studies indicate that intrauterine growth restriction (IUGR) following uteroplacental insufficiency (UPI) reduces nephron number and predisposes toward renal insufficiency early in life and increased risk of adult-onset hypertension. In this study, we hypothesized that the inducible enzyme cyclooxygenase-2 (COX-2), a pivotal protein in nephrogenesis, constitutes a mechanism through which UPI and subsequent glucocorticoid overexposure can decrease nephron number. We further hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 66 publications
(77 reference statements)
0
44
0
Order By: Relevance
“…Sex differences at the molecular level also persist from embryonic into fetal life. Baserga et al (8) have reported that gestation in the rat cyclooxygenase-2 (COX-2) levels were higher in the female than the male kidney at day of gestation (DG) 8, although not significantly increased at DG 21. In contrast, 11␤-hydroxysteroid dehydrogenase 2 (11␤-HSD2) levels were higher in the male control kidney at DG 21.…”
Section: Innate Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences at the molecular level also persist from embryonic into fetal life. Baserga et al (8) have reported that gestation in the rat cyclooxygenase-2 (COX-2) levels were higher in the female than the male kidney at day of gestation (DG) 8, although not significantly increased at DG 21. In contrast, 11␤-hydroxysteroid dehydrogenase 2 (11␤-HSD2) levels were higher in the male control kidney at DG 21.…”
Section: Innate Sex Differencesmentioning
confidence: 99%
“…In contrast, 11␤-hydroxysteroid dehydrogenase 2 (11␤-HSD2) levels were higher in the male control kidney at DG 21. Both of these gene products play important roles in renal function, and alterations in either could have developmental and/or functional effects in the kidney (8). We have recently shown that considerable sex differences are observed in the response to maternal nutrient restriction (MNR) between male and female baboon fetuses near term (19).…”
Section: Innate Sex Differencesmentioning
confidence: 99%
“…To test these hypotheses, we used a well-characterized rat model of UPI-induced IUGR (31,33,34), which results in significantly lighter placental mass and pup body weights compared with controls (54,64). IUGR rat pups grow up to develop metabolic disorders and impaired neurodevelopment (4,8,12,39,62,79). Furthermore, circulating corticosterone and testosterone levels are elevated in male IUGR rat pups at birth and postnatal day 21 (2,3,53), suggesting a sex-specific impairment of the HPA axis.…”
mentioning
confidence: 99%
“…TO THE EDITOR: I read with great interest the paper of Baserga et al (1), which describes the effect of uterine artery ligation in the pregnant rat on fetal cyclooxygenase-2 (COX-2) expression and blood pressure. This is an important subject and the study presents interesting results, but I would like to comment on some parts of their study.…”
mentioning
confidence: 99%
“…Of interest, dams after uterine artery ligation do not provide a normal lactational environment in combination with a low number of pups per litter, as this leads to a less stimulated milk production and therefore to postnatal growth restriction (9). Baserga et al (1) culled litters to six pups only, which would have been of influence on the milk quantity and/or quality. As no data on the body weight were provided, the influence of the postnatal environment on the results cannot be determined.…”
mentioning
confidence: 99%